Theoretical study on optoelectronic properties of GaAs nanostructures. (February 2021) - Sun, Yan; Liu, Lei; Lv, Zhisheng; Zhangyang, Xingyue; Lu, Feifei; Tian, Jian
Abstract: In this paper, GaAs frustum of a cone, cone, frustum of a hexagonal pyramid and hexagonal pyramid array models were designed (frustum is a portion of a cone or pyramid after the top is removed), and the influence of geometric parameters on the photoelectric emission characteristics was studied. And we used MATLAB to calculate and analyze the influence of geometric parameters on the carrier distribution and quantum efficiency of nanostructures. It is found that increasing the bottom diameter of the pyramid can effectively improve the optoelectronic characteristics of the photocathode. Compared with the cone structure, the frustum structure array has better light absorption characteristics in the short wave region, and has better quantum efficiency.